A Futuristic STEAM-Integrated PBL Model Enhanced by Digital Technology to Foster High School Students’ Creative Thinking in Physics Learning - Winda Wulan Sari; Dwikoranto Dwikoranto; Lindsay N. Bergsma (Universitas Negeri Surabaya, 2025)
Objective: This study aims to analyze the profile of the STEAM-integrated PBL model specifically designed to encourage creative thinking in high school students while learning physics. Method: The research method used is a literature study (literature review) conducted by collecting several previous research journals related to the material. Results: The results of this study indicate that using the STEAM-integrated PBL model improves students' creative thinking. In addition, STEAM learning, teachers, or educational institutions will help the progress of the Indonesian education system. Because the application of STEAM learning can prioritize problem-solving-based learning, especially in physics learning related to everyday life. Novelty: The novelty obtained is that STEAM-PBL Integration as an Effective Approach can Increase Student Creativity compared to conventional methods, STEAM-PBL Has a Broad Impact on Critical Thinking and Problem Solving Skills through a challenge-based approach. Then, the role of technology and digital media in strengthening STEAM-PBL learning by increasing concept understanding and student engagement. Moreover, the Importance of contextualization in STEAM-PBL Learning is easier to understand and increases student interest in learning.